(untitled) (Journal of Fatima Jinnah Medical University, 2024)
Background: Primary Post-partum haemorrhage (PPPH) is the multi-factorial and the leading cause of maternal mortality. The following study is set to identify prevalence and factors related to it among women delivering in a tertiary care hospital in Lahore. Patient and methods: A cross-sectional study was conducted in the Departments of Obstetrics and Gynaecology, Services Hospital Lahore from January to June 2021. Data was collected on a structured questionnaire from three hundred and forty-eight women and their medical records using a non-probability purposive sampling technique. The variables included socio-demographics, antepartum, and intrapartum characteristics. Assessment of PPPH was carried out by primary obstetrician, by visual estimation and data was entered on SPSS version 23.0. The chi-square test was used as a test of significance, and binary regression was applied. A p-value <0.05 and Odds’ Ratio >2 was taken as significant. Results: Ninety-nine out of the total (28.4%) had PPPH. Illiteracy and low socio-economic status (income value less than the median) had significant associations with PPPH (AOR 4.26 p-value=0.015, CI 1.322-13.684) (OR 0.146, p-value=0.005, CI 0.259-0.789), respectively. A statistically significant association was found between PPPH and uterine atony (p-value=0.000, AOR=39.88, CI=60.84-2628.12), placental complications (p-value 0.035, AOR=3.321, CI=1.091-10.11), fatal demise (p-value 0.000, AOR=31.89, CI=7.99-128.243) and PIH (p-value 0.028, AOR=0.341, CI=0.130-0.892). Conclusion: This study showed a high prevalence of PPPH. Illiteracy, socioeconomics, uterine atony, placental complications, and fetal demise were significant contributors. These findings highlight the importance of socio-demographics and good management of the third stage of labour. Further research with a larger sample size can refine these insights for the development of targeted preventive strategies.